Feast and famine food and nutrition in Ireland, 1500-1920 - Clarkson, Leslie A. (Oxford University Press, 2001)
This text traces the history of food and famine in Ireland. The authors explore the economic and social forces which have lain behind changes in diet, as well as the more personal motives of taste, preference, and nutrition.